Correlation of Arterial Blood Gas and Serum Electrolyte Levels in Neonates Admitted to the Neonatal Intensive Care Unit - Aashna Darshanbhai Shah; Dharaben N Kanani; Kaushik S Chaudhari; Vishva Darshanbhai Shah; Mayurkumar Goradhanbhai Makadia; Dipika Sathvara (RGUHS Journal of Medical Sciences)
Background and Objectives Neonates admitted to the intensive care units are susceptible to developing electrolyte imbalances which can result in an increased mortality rate. Measuring electrolyte levels particularly sodium Na and potassium K is often necessary in seriously ill patients. The present study aimed to compare the concentration of sodium and potassium between the arterial blood sample and serum from the venous blood sample.Methods We retrospectively studied 100 hospitalized neonates in the Neonatal Intensive Care Unit NICU whose samples were taken for ABG and serum electrolytes simultaneously and both samples were processed on GEM PREMIER 3000 and Roche AVL 9180 Electrolyte Analyzer respectively. Statistical measures employed to compare the data included the Pearson correlation coefficient and Bland-Altman plots.Results The mean concentration of sodium Na was 135.05 mmolL SD 6.69 mmolL using the ABG and 135.36 mmolL SD 6.54 mmolL using the serum sample. The mean level of the K was 3.91 mmolL SD 0.86 mmolL using the ABG and 4.12 mmolL SD 0.91 mmolL using the serum sample. The associated correlation coefficients were 0.89 and 0.88 respectively.Conclusion We conclude that the results for Na and K are like those of the ABG sample and serum from the venous blood sample. So one can decrease the amount of blood sample volume and the number of needle punctures required for electrolytes assessment in neonates admitted to the NICU.